Exploring the utility of state-level wise reasoning: New assessment and facilitation methods - Brienza, Justin Peter (University of Waterloo, 2017)
Wisdom is considered the apex of human development, exemplified in various cultural traditions by optimal, balanced judgment and decision making that benefits others and the self. Contemporary psychological accounts suggest that practicing wisdom through reasoning (i.e., intellectual humility, recognition of uncertainty and change, consideration of the broader context at hand and perspectives of others, integration of these perspectives/compromise) can help people to adaptively navigate everyday social challenges, yet large-scale empirical investigation on this topic is lacking. In this dissertation, I introduce and validate a new method to assess situation-specific wise reasoning. To encourage future research on the topic, I establish an initial nomological network of individual differences around wise reasoning and show its relations to fundamental constructs, including increased cooperation and reduced bias. I also show that experimentally enhancing wise reasoning can result in more cooperative, balanced attitudes and emotions (e.g., reduced attitude polarization; greater tolerance for outgroups). The findings presented in this dissertation suggest that wise reasoning can help people to navigate everyday social challenges. Implications for theory, future research, and practical applications for wise reasoning are discussed.
Keywords: conflict; wisdom; reconstruction method; balance; reasoning; bias; decision making